PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 05 PUSAKO SIAK (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study was motivated by the percentage of students who achieve KKM 70 at mid even semester of 2014 to 2015 year education is even lower. From 20 students only 8 people (40.00%) of students who reach KKM and 12 (60.00%) students who have not reached KKM (minimum completeness criteria)with an average of 63.50. This is because teachers still often using conventional methods / lectures and do not use learning models, do not involve students in the learning process only centered on the teacher, the teacher never guide the students while working on assignment, the teacher still form a study group as homogeneous, thus causing student bored, do not want to ask, feel difficulty in doing the task, and that only those who are good students are more active. Of these problems is necessary to study a class action by applying Jigsaw cooperative learning model. Where the research is at primary school 05 Pusako Siak with research subjects are students of class IV and as many as 20 people, boys 9 and 11 female students. This study was carried in 2 cycles. Instrument collecting data in this study is the observation sheet teacher activity, student activity observation sheet and test sheet daily tests. Observation results showed that the activity of teachers and students has increased. The activities of teachers in the first cycle both categories increased 61.54% in the second cycle into 85.58% very good category. Activity of students in the first cycle both categories increased 61.36% in the second cycle into 84.09% very good category. The results showed that the learning outcomes of students has increased, the initial score with an average of 63.50 incomplete categories increased in the first cycle to 69.50 categories is not exhaustive, and the second cycle increased to 77.50% complete category. Mastery learning students on the basis of a score of 40.00%, which reached KKM, in the first cycle showed that 50.00% of students who reach the KKM has been established, on the second cycle increased to 75.00% of students who reach KKM and completeness predetermined percentage , From the above shows that through the implementation of Jigsaw cooperative learning can improve learning outcomes IPS Elementary School fourth grade students in lesson 05 Pusako Siak 2014-2015.Keywords: cooperative learning model jigsaw, IPS learning outcomes